A REVIEW ON SMART CAMPUS CONCEPT AND APPLICATION TOWARDS ENHANCING CAMPUS USERS’ LEARNING EXPERIENCES - Mohd Rahim, Faizul Azli; Zainon, Nurshuhada; Aziz, Nur Mardhiyah; Chuing, Loo Siaw; U.H. Obaidellah (International Journal of Property Sciences (E-ISSN: 2229-8568), 2021)
The smart campus is an emerging trend that allows universities to improved services, decision making and campus sustainability. The recent pandemic has directed and amplified the need for a paradigm shift, with predominant virtual teaching, and remote working bursting onto the scene. As an educational institution, understanding campus user’s learning experience is vital in the process of assessing and ensuring quality university studies. Therefore, this study provides a review of smart campus concept, application and potential opportunities that emerge in the smart campus towards enhancing campus users’ learning experiences. To achieve the purpose of the study, a systematic literature review has been conducted extracted from the Scopus database. Initially, 19 articles were gathered. After the screening process using the inclusion and exclusion criteria, 16 articles were screened and finally, 11 articles were included in the review. This study found that smart campus is an integral concept that needs to be developed and applied in universities. Besides that, several potential opportunities emerging from the smart campus application such as the application of augmented reality and virtual reality in facilitating the learning process, the exploration of daily internet traffic that enables traffic forecasting to improve network service and personalised services. Thus, this study helps to explore the potential fields of employing smart campus especially in the learning process among community campus.